Buckling Of Imperfect Cylinder-Cone-Cylinder Transition Under Axial Compression - Ifayefunmi, Olawale Friday; Ismail, Mohd Shahrom; Sheikh Md Fadzullah, Siti Hajar (Elsevier Ltd, 2019)
This paper presents the numerical investigation results focusing on the buckling behavior of geometrically imperfect cylinder-cone-cylinder transition subjected to axial compression. The models are assumed to be made from unalloyed mild steel. Several initial geometric imperfections techniques such as (i) Eigenmode imperfection approach, (ii) Axisymmetric outward bulge and (iii) Single Perturbation Load Analysis (SPLA) imperfections were superimposed on the perfect cylinder-cone-cylinder shell. Reduction of the buckling strength was then quantified numerically. As expected, the buckling strength of cylinder-cone-cylinder shells was strongly affected by initial geometric imperfection and the reduction in buckling strength was seen to be strongly dependent on the approach and the location of imperfection. Eigenmode imperfection is seen to produce the lowest knockdown factor, followed by axisymmetric outward bulge and SPLA imperfections, respectively. Finally, the lower bound knockdown factors that can be implemented for design purposes has been proposed for the worst initial geometric imperfection case, i.e., Eigenmode, imperfections.